Respuesta :

Hello from MrBillDoesMath!

Answer:

y = -6x +  360

Discussion:

Suppose that y = mx + b.  From the first table row when x = 0, y = 360. Substituting these in the equation gives

y = mx + b

360 = m(0) + b => b = 360

So far then y = mx + 360.   From the second row of the table

we know that y = 300 when x = 10. Substituting this in y = mx + 360 gives

y = mx + 360

300 = m(10) + 360 =>

300 - 360 = 10m =>

-60  = 10m =>

m = -6

Conclusion: the equation is y = -6x +  360

BUT we should substitute the values from the other rows into this equation to make sure the data provided is linear. (Remember: table data can lie. Only MrBill doesn't lie! );


3rd row:  Does 240 = -6(20) + 360 = -120 + 360 - 240  . Yes

4th row: Does 180 = -6(30) + 360 = -180 + 360 = 180.  Yes

5th row: Does 120 =  -6(40) + 360 = -240 + 360 = 120. Yes


Thank you,

MrB